2022
DOI: 10.1021/acsomega.2c03563
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetry Study of Noble Metals and Their Alloys for Use in Implantable Electrodes

Abstract: Innovation in the application and miniaturization of implantable electrodes has caused a spike in new electrode material research; however, few robust studies are available that compare different metal electrodes in biologically relevant media. Herein, cyclic voltammetry has been employed to compare platinum, palladium, and gold-based electrodes’ potentiometric scans and their corresponding charge storage capacities (CSCs). Ten different noble metals and alloys in these families were tested under pseudophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, using Gold as a stimulation electrode in vivo presents electrochemical limitations. Gold electrodes tend to exhibit lower charge storage and charge injection capacities relative to Platinum and Iridium electrodes [ 33 ]. In addition, Gold is susceptible to dissolution under a high current density and high frequency stimulation conditions, particularly during the anodic phase of stimulation pulsing [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, using Gold as a stimulation electrode in vivo presents electrochemical limitations. Gold electrodes tend to exhibit lower charge storage and charge injection capacities relative to Platinum and Iridium electrodes [ 33 ]. In addition, Gold is susceptible to dissolution under a high current density and high frequency stimulation conditions, particularly during the anodic phase of stimulation pulsing [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters for a non-Faradaic reaction are desired in electrode implantation to promote biostability of the electrode, and are represented as the water window as shown in Figure 10 . Similar to EIS, CV requires a working electrode, a counter electrode, a reference electrode, and an electrolyte ( Elgrishi et al, 2018 ; Jerkiewicz, 2022 ; Puglia and Bowen, 2022 ). During the execution of this technique, a triangular potential waveform is applied, while measuring the current between the working and counter electrodes.…”
Section: Neural Interfaces ( a G Hernández M A González-gon...mentioning
confidence: 99%
“…The electrochemically active surface area (ECSA) of the electrode surfaces was determined from cyclic voltammograms recorded in degassed H 2 SO 4 0.5 M solution at room temperature with potentials between −0.6 and 1.5 V at a scan rate of 50 mV s –1 . The values of the ECSA and the amount of the Pt catalyst ( m Pt ) in the samples can be estimated as follows , m Pt = Q H M 4 F ECSA = Q H .25em ( μ C ) m Pt × 210 .25em μ C .25em normalc m 2 .25em ( normalm 2 normalg 1 ) where Q H is the amount of charge that varies along the surface of Pt during the hydrogen adsorption–desorption process, M is the atomic weight of Pt (195.09 g mol –1 ), and F is the Faraday constant (96485.309 C mol –1 ).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The charge of the hydrogen adsorption−desorption process (Q H ) was estimated from the integral of the peak area shown in the current vs time plot (Figure S5). 31 The ECSA S Pt was then extracted from hydrogen adsorption−desorption charge as mentioned above (Table 2). It was found that the value of S Pt on GNH@PtNPs is about 2.4× larger than that on GSH@PtNPs.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%